ANALISIS GAYA BELAJAR SISWA SECARA VISUAL, AUDITORI DAN KINESTETIK TERHADAP PRESTASI BELAJAR MATA PELAJARAN IPA - Jima, Maria Julita; Fitriah, Fitriah; Solo, Yuliana Dua (Teaching and Learning Journal of Mandalika (Teacher) e- ISSN 2721-9666, 2024)
This study aims to determine students' visual, audiotonal and kinesthetic learning styles on students' learning achievement, in class VIII B science subjects at SMP Negen 1 Mego. This research was conducted from 1 February to 28 February 2023. The method used is descriptive qualitative with percentages. Data collection was obtained through observation, questionnaires, interviews and documentation. From the analysis of visual, audiotonal and kinesthetic learning styles on student achievement that has been studied, the following results are obtained, visual learning styles during the learning process are included in the "Enough" category with a percentage of 65%, auditory learning style learning styles during the learning process are included in the "Enough" category. with a percentage of 62.22%, the kinesthetic learning style learning style during the learning process is included in the "Good" category with a percentage of 66.85% The most student learning style is the kanesthetic type. achieving learning mastery the learning achievement of the three learning styles is the most successful learning style audiotone.